2012
DOI: 10.5923/j.arch.20120202.03
|View full text |Cite
|
Sign up to set email alerts
|

Workplace and Productivity: A Post Occupancy Evaluation of LAUTECH Senate Building, Ogbomoso, Nigeria

Abstract: Post occupancy evaluations (POE) have been discovered to be of high importance in building design decisions. The study explored POE to assess the users' satisfaction with the office spaces of Ladoke Akintola University of Technology (LAUTECH) Senate Building, Ogbomoso, Nigeria. The aim was to measure the influence of workplace design quality on workers' productivity to inform future design decisions. A questionnaire survey of 150 randomly sampled office workers in the building was carried out. The variables in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…PostOccupancy Evaluation method as stated by Adedeji and Fadamiro (2012); Zimmerman and Martin (2001),is generally accepted for obtaining opinion of users and observation studies in the built environment. Northern Nigeria has vast area in terms of landmass and the significant developments are in state capitals.…”
Section: Methodsmentioning
confidence: 99%
“…PostOccupancy Evaluation method as stated by Adedeji and Fadamiro (2012); Zimmerman and Martin (2001),is generally accepted for obtaining opinion of users and observation studies in the built environment. Northern Nigeria has vast area in terms of landmass and the significant developments are in state capitals.…”
Section: Methodsmentioning
confidence: 99%
“…Motor parks have not met the needs of their users in Minna because they are inadequate and require major transformation (Adedayo and Zubairu, 2013). Another study by Adeniran and Akinlabi, (2012) suggested that because of the form adopted in the architectural design of the Senate Building under study, satisfactory levels of indoor environmental comfort was not achieved and appeared to have been sacrificed for the high aesthetic value achieved.…”
Section: Post Occupancy Evaluation: the Nigerian Casementioning
confidence: 99%